The status, challenges and opportunities of civil registration and vital statistics in Ethiopia: a systematic review - Gizaw, Muluneh E. (International Journal of Scientific Reports, 2020)
While civil registration and vital statistics (CRVS) plays prominent roles to improve public sector management, i.e., the economic, social and political issues of a population, its adoption has not been yet without challenges and is still in its infant stage in most developing countries, including Ethiopia. This study reviews various literatures and studies made by different researchers and institutions related to the status, challenges and opportunities of CRVS in Ethiopia. Even though, CRVS has got a national recognition before hundred years in the country, the directives and rules are not issued for implementation. According to the findings, Ethiopia is among the countries that have not yet installed CRVS systems in both national and regional levels successfully. It is challenged by infrastructure, capacity building and lack of awareness among the population on the benefits of the system. The status of civil registration and vital statistics is in the lowest rank in Ethiopia. Recently, the aid agencies and the government has been giving special attention to scale up its performance in different parts of the country.